2012
DOI: 10.1093/nar/gks616
|View full text |Cite
|
Sign up to set email alerts
|

A highly specialized flavin mononucleotide riboswitch responds differently to similar ligands and confers roseoflavin resistance to Streptomyces davawensis

Abstract: Streptomyces davawensis is the only organism known to synthesize the antibiotic roseoflavin, a riboflavin (vitamin B 2 ) analog. Roseoflavin is converted to roseoflavin mononucleotide (RoFMN) and roseoflavin adenine dinucleotide in the cytoplasm of target cells. (Ribo-)Flavin mononucleotide (FMN) riboswitches are genetic elements, which in many bacteria control genes responsible for the biosynthesis and transport of riboflavin. Streptomyces davawensis is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 25 publications
1
73
0
1
Order By: Relevance
“…The functions of the genes ribB-ribM, ribG, and monofunctional ribA have been verified experimentally in an earlier work (18). Moreover, it was recently shown that the ribBMAH genes are controlled at the level of translation by an FMN riboswitch (ribB FMN riboswitch, or RFN element) located directly upstream of ribBMAH (47).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The functions of the genes ribB-ribM, ribG, and monofunctional ribA have been verified experimentally in an earlier work (18). Moreover, it was recently shown that the ribBMAH genes are controlled at the level of translation by an FMN riboswitch (ribB FMN riboswitch, or RFN element) located directly upstream of ribBMAH (47).…”
Section: Resultsmentioning
confidence: 80%
“…In addition, non-protein cellular targets for RoFMN were discovered. According to these works, RoFMN reduces expression of genes controlled by FMN riboswitches in B. subtilis, Streptomyces coelicolor, and the human pathogen Listeria monocytogenes (33,35,46,47). FMN riboswitches are genetic elements involved in the regulation of riboflavin biosynthesis and transport (62).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A DNA fragment coding for Rli96 was produced by PCR using the modifying oligonucleotides 5=-CGC AAA GCT TAT AAA TAA AAC CAG CTA ATT-3= and 5=-ATA TAT GCG GCC GCT CAT TGA ATA ATT CTT CAT TG-3=. The PCR product was digested and ligated to linearized pT7-luc (7). Construction of the recombinant strain L. monocytogenes M1 (a L. monocytogenes EGDe derivative) was described earlier (17).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the FMN riboswitch variant in C. difficile, other FMN riboswitch variants have been identified in a previous study (Pedrolli et al 2012). One such representative appears to have evolved to functionally discriminate against the natural FMN analog called roseoflavin phosphate, a compound that exhibits antibacterial properties.…”
Section: Orphan and Other Riboswitch Candidatesmentioning
confidence: 97%